2019
DOI: 10.5860/crl.80.6.876
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Perceptions and Use of Google Scholar and Academic Library Discovery Systems

Abstract: Google Scholar and academic library discovery systems are both popular resources among academic users for finding scholarly information. By conducting an online survey with 975 users from more than 20 public research universities across the United States, this study comparatively investigates how and why academic users use these two resources. Results show that the ways participants used both resources were similar, and both were perceived as highly accessible and useful. Academic library discovery systems' pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…With regards to the resulting model in this study postgraduate participants appear to perceive Performance and Effort Expectancy as stronger determinants of use, and certainly over the social and organisational influences of their peers and by the perception of the university's facilitating use in its provision of the search tool in the e-library. This would concur with the findings of previous studies such as Oh and Colón-Aguirre (2019) and Cothran (2011) highlight the task orientation of the factors influencing use of GS. The influence of the perception of the task performance and effort is further explored with the inclusion, in this study, of the 'Individual' factors, SE, DK, CE and MO, and of the 'System' factors of VI, AC, RE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With regards to the resulting model in this study postgraduate participants appear to perceive Performance and Effort Expectancy as stronger determinants of use, and certainly over the social and organisational influences of their peers and by the perception of the university's facilitating use in its provision of the search tool in the e-library. This would concur with the findings of previous studies such as Oh and Colón-Aguirre (2019) and Cothran (2011) highlight the task orientation of the factors influencing use of GS. The influence of the perception of the task performance and effort is further explored with the inclusion, in this study, of the 'Individual' factors, SE, DK, CE and MO, and of the 'System' factors of VI, AC, RE.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Cothran's (2011) study involving undergraduate students found SI of the peer group and student tutors was a key influencing factor, motivating use. Further, Cothran's (2011) suggested loyalty as a factor and found that people's use of Google for searching the web has reported the influence of others and the perceived popularity of the engine to be key determining factors (Oh and Colón-Aguirre, 2019). Facilitating conditions (FC) are defined by Venkatesh et al (2003) as “ the degree to which an individual believes that an organizational and technical infrastructure exists to support the use of a system” (p. 453).…”
Section: Methodsmentioning
confidence: 99%
“…Scholarly information discovery is certainly a case in point. Thus, the long-established popularity of Google Scholar and Google and their embeddedness in the scholarly field (Blankstein & Wolff-Eisenberg, 2019;Oh & Colón-Aguirre, 2019) are confirmed, despite the long and continuing criticisms levelled against them (Lynch, 2016;Miller & Record, 2017;Schneier, 2015). Google Scholar, however, is not as relied upon in the arts and humanities, a finding found elsewhere (Blankstein & Wolff-Eisenberg, 2019;Wolff, Rod, & Schonfeld, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…e important criteria for assessing discovery systems and valuable lessons that may be applied in future system-evaluation processes and implementations should be identified in pursuit of better options for users and improved access to e-resources. A recent study by Oh and Colón-Aguirre [26] on the perceptions for use of Google Scholar and academic library discovery systems reveals that the perceived comprehensiveness, subjective norm, loyalty, and intended use of academic library discovery systems are higher than Google scholar, while at the same time, the perceived ease of use, satisfaction, and system quality of Google Scholar were higher than those of academic library discovery systems, implying that users' satisfaction with the DL is the key indicator for the quality of DL services.…”
Section: The Quality Of Service In Digital Librariesmentioning
confidence: 95%